DEVELOPING STUDENTS’ SPEAKING COMPETENCE BY USING SEMANTIC MAPPING THROUGH COLLABORATIVE LEARNING TECHNIQUE - Syafrizal, Syafrizal; Safnil, Safnil; Dharmayana, I Wayan (TRIADIK, 2017)
Abstract: Semantic mapping has been demonstrated as practical teaching and learning technique for students at all grade levels. However, its use for speaking class has been relatively unexplored. The objective of this study is to investigate the influence of semantic mapping as a technique to improve students’ speaking ability. The research design of this study was quasi experimental design. The population comprised the seventh grade students of SMP Taba Renah, Musi Rawas in the academic year of 2015/2016 and the sample consisted of 44 students. The data were collected via test, observation and interview. In analyzing the data, for the pre-test it was found that there were not significant differences in speaking competence and its components in experimental and control class because P > 0.05. For the post-test, it was found that for total speaking competence P-value is 0.018, for vocabulary in speaking P-value is 0.001, for fluency in speaking P-value is 0.033, for pronunciation in speaking P-value is 0.060, and for grammar in speaking P-value is 0.348. So, there were significant differences in experimental & control class in vocabulary and fluency aspects because P < 0.05 but there were not significant difference in pronunciation and grammar aspects because P > 0.05. The finding shows that semantic mapping as technique is effective to be implemented in teaching English to improve students’ speaking ability, especially in vocabulary and fluency aspects but it is not in pronunciation and grammar